2017
DOI: 10.1002/2017gl073018
|View full text |Cite
|
Sign up to set email alerts
|

Non‐self‐similar source property for microforeshocks of the 2014 Mw 6.2 Northern Nagano, central Japan, earthquake

Abstract: Foreshocks are considered as part of the preparation process for large earthquakes and, as such, can provide important constraints on earthquake generation. We examine the characteristics of the 4 day long foreshock sequence of the 2014 Northern Nagano earthquake (Mw 6.2) using seismograms recorded by a dense seismic observation network including data from a deep borehole closest to the foreshock region. The improved earthquake catalog shows a slow‐speed migration of the sequence toward the main shock hypocent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Earthquake source spectra are often modelled to investigate the finite source attributes of earthquakes (e.g. Houston & Kanamori 1986;Houston 1990;Prieto et al 2004;Baltay et al 2010;Chen & Shearer 2011Baltay et al 2013;Uchide et al 2014;Goebel et al 2015;Imanishi & Uchide 2017). Two key parameters describing an earthquake spectrum are the average corner frequency (f c ) and fall-off exponent (n).…”
Section: Corner Frequency (F C ) and Fall-off Exponent (N)mentioning
confidence: 99%
See 1 more Smart Citation
“…Earthquake source spectra are often modelled to investigate the finite source attributes of earthquakes (e.g. Houston & Kanamori 1986;Houston 1990;Prieto et al 2004;Baltay et al 2010;Chen & Shearer 2011Baltay et al 2013;Uchide et al 2014;Goebel et al 2015;Imanishi & Uchide 2017). Two key parameters describing an earthquake spectrum are the average corner frequency (f c ) and fall-off exponent (n).…”
Section: Corner Frequency (F C ) and Fall-off Exponent (N)mentioning
confidence: 99%
“…The geometric mean is performed here to have the arithmetic mean of the spectra in the log space. Finally, we apply a nonlinear least-squares algorithm to fit the spectra from ∼5 to ∼35 Hz with the Boatwright spectral model assuming γ = 2 (Boatwright 1980;Huang et al 2017;Imanishi & Uchide 2017). The spectra fitting range is suggested in Huang et al (2017) for M2-induced earthquakes in Arkansas.…”
Section: Corner Frequency (F C ) and Fall-off Exponent (N)mentioning
confidence: 99%
“…In contrast, observations suggesting a break in self-similarity have been reported in local studies (e.g. Harrington & Brodsky, 2009;Bouchon et al, 2011;Lin et al, 2016;Imanishi & Uchide, 2017;Trugman & Shearer, 2017;H. Wang, Ren, Wen, & Xu, 2019;Mayeda, Malagnini, & Walter, 2007;Bindi, Spallarossa, Picozzi, & Morasca, 2020), even though their interpretation is hampered by well known artifacts due to trade-offs between path and source effects and attenuation of high-frequencies (Abercrombie, 1995;Ide, Beroza, Prejean, & Ellsworth, 2003;Abercrombie, 2021).…”
Section: Introductionmentioning
confidence: 90%
“…Stress drop has been found to be independent of magnitude by multiple studies, and compilations of studies, covering different magnitude ranges, from small and moderate (Allmann & Shearer, 2007;Goebel et al, 2015;Imanishi & Ellsworth, 2006;Uchide et al, 2014) to large ones (Allmann & Shearer, 2009). In contrast, other studies have reported non-self-similarity, typically over smaller magnitude ranges (Bindi, Spallarossa, et al, 2020;Imanishi & Uchide, 2017;Mayeda et al, 2005;Oye et al, 2005). Spatial and temporal variations of stress drop have the potential to reveal heterogeneities and changes in stress distribution within fault zones (e.g., Allmann & Shearer, 2007;Chaves et al, 2020;Chen & Shearer, 2013;Moyer et al, 2018;Ruhl et al, 2017;Shearer et al, 2006;Uchide et al, 2014).…”
mentioning
confidence: 99%